Advancements and Future Directions in Yellow Rice Wine Production Research - Zhang, Jingxian; Li, Tian; Zou, Gen; Wei, Yongjun; Qu, Lingbo (Fermentation (Basel), 2024)
Yellow rice wine is a traditional fermented beverage in China. The microorganisms in the brewing process play a crucial role in shaping the composition and quality of the wine through their regulation of microbial growth, fermentation metabolites, metabolic balance, and ethanol production. Yellow rice wine not only has culinary value but also possesses potential medicinal value. This is attributed to the presence of polyphenolic compounds, antioxidants, and other natural products that can provide antioxidant and other probiotic effects. The fermentation process of yellow rice wine offers potential nutritional supplementation and improved digestion. While traditional brewing techniques have long been employed, modern biotechnology helps enhance the quality and stability of the wine by selecting suitable microbial strains, optimizing fermentation conditions, and precisely controlling the fermentation process. The collection of diverse fermentation microbes and the construction of specifically designed microbiota for yellow rice wine production could expedite the production of high-quality yellow rice wine. The ultimate goal is to enhance the nutritional value, conditioning function, and overall consumption experience of yellow rice wine. Future research will delve into exploring the relationship between microorganisms and active ingredients in yellow rice wine, improving both the quality and functionality of the wine.